Morphological characteristics and atomic evolution behavior of nanojoints in Ag nanowire interconnect network. (1st June 2023) - Cui, Jianlei; Ren, Xiaoying; Mei, Xuesong; Fan, Zhengjie; Huang, Chenchen; Wang, Zhijun; Sun, Xiaofei; Wang, Wenjun
Abstract: Ag nanowires (AgNWs) have shown great application value in the field of flexible electronics due to their excellent optical and electrical properties, and the quality of its joints of AgNWs in the thin film network directly plays a key role in its performance. In order to further improve the joint quality of AgNWs under thermal excitation, the thermal welding process and atomic evolution behavior of AgNWs were investigated through a combination of in situ experimental and molecular dynamics simulations. The influence of processing time, temperature, and stress distribution due to spatial arrangement on nanojoints was systematically explored. What is more, the failure mechanisms and their atomic interface behavior of the nanojoints were also investigated. Highlights: Three different types of nanojoints are fabricated at low-temperature in a vacuum. The failure mechanisms of the nanojoints at high-temperature are revealed. The atomic interface behaviors at nanojunctions are revealed. The molecular dynamics models are established to predict joint configurations.